Analyses of particle size and abrasive water jet drilling of synthesized chromel metal matrix. (2020) - Anix Joel Singh, J.; Vishnu Vardhan, T.; Vairamuthu, J.; Stalin, B.; Subbiah, Ram
Abstract: The chromel was one type of nickel-based metal matrix (MMC) and it was fabricated through stir casting technique. The titanium carbide (TiC) was used as a reinforcement material. The particles were analyzed through Atomic Force Microscopy (AFM) and Dynamic Light Scattering (DLS). Abrasive Water Jet Drilling (AWJD) was mechanical energy based non-traditional process that was applied to pierce the stir casted chromel MMC. During the drilling process, jet pressure, traverse speed, and standoff distance were pointed as the main input factors. The Material Subtraction Rate (MSR) and Surface Finish (SF) have been chosen as the response factors. The effect of factors and their correlation were validated through variance test and interface plots.